A Prospective Comparison of Vertebral Column Decancellation Versus Pedicle Subtraction Osteotomy in Thoracolumbar Kyphosis (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: ankylosing spondylitis; kyphosis; vertebral column decancellation (VCD); Osteotomy; posterior approach